Pengukuran Panjang Koherensi Menggunakan Interferometer Michelson - Setyaningsih, Agustina; Marhaendrajaya, Indras; Firdausi, K. Sofjan (BERKALA FISIKA, 2007)
A simple measurement of coherence length of He-Ne laser, red diode laser, and green diode laser using Michelson interferometer has been conducted. The steps in this research were setting up the Interferometer by places movable mirror on mirror rail. To determine the coherence length of the laser’s light, movable mirror has been shifted until the interference fringes disappear on the screen. Results of measurement for the coherence length of He-Ne laser I is cm, He-Ne laser II is cm, red diode laser I is cm, and green diode laser II is cm. Keywords: Coherence, coherence length.